2019
DOI: 10.1103/physreva.99.033419
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of the time evolution of field-free molecular orientation by THz laser pulses

Abstract: We present a theoretical study of the shaping of the time-evolution of field-free orientation of linear molecules. We show the extend to which the degree of orientation can be steered along a desired periodic timedependent signal. The objective of this study is not to optimize molecular orientation but to propose a general procedure to precisely control rotational dynamics through the first moment of the molecular axis distribution. Rectangular and triangular signals are taken as illustrative examples. At zero… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…2(a) and 2(b), which are before and after 0 ps, respectively]. This transient orientation induced by single THz pulses is expected and has been observed before [41][42][43][44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 55%
“…2(a) and 2(b), which are before and after 0 ps, respectively]. This transient orientation induced by single THz pulses is expected and has been observed before [41][42][43][44][45][46][47][48].…”
Section: Resultsmentioning
confidence: 55%
“…Whereas either adiabatic interactions [26][27][28][29][30][31][32][33][34][35][36][37][38] or their impulsive, non-adiabatic counterparts [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] have received much attention, interactions with finiteduration pulses have been scarce [54][55][56]. It is the last that are the focus of the present study.…”
Section: Introductionmentioning
confidence: 94%
“…Despite the slow progress in experiments, several theoretical proposals have been directed toward the realization of molecular field-free orientation by exclusively using zeroarea terahertz pulses [36][37][38][39][40]. Furthermore, recent theoretical work has shown that a single half-cycle-zero-area terahertz pulse can result in steady molecular orientation a long time after the pulse is turned off [41].…”
Section: Introductionmentioning
confidence: 99%